PENGARUH DISPLAY PRODUK DAN ULASAN PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN PADA PT. BOGA ABADI PRIMA MEDAN - Azzura, Syarla; Sahputra, Ngatno; Rahim, Rani (Journal Economic Management and Business, 2025)
This study aims to analyze the influence of product display and customer reviews on purchase decisions at PT. Boga Abadi Prima Medan. A quantitative research method was employed, using a survey of 95 consumers. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that both product display and customer reviews have a significant influence on purchase decisions, both individually (partially) and jointly (simultaneously). The coefficient of determination shows that 87.5% of the variation in purchase decisions is explained by these variables, while the remaining 12.5% is attributed to other factors.